The 20% of petai seed (Parkia speciosa) extract cream in inhibited the increase of melanin counts in the skin of guinea pigs (Cavia porcellus) exposed to ultraviolet B - Nining Triyana Darise; Wimpie Pangkahila; AAGP Wiraguna (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: The exposure to UV may cause skin disorders, including hyperpigmentation. Petai seeds are categorized as traditional medicinal plants that have anti-inflammatory and antioxidant effects, such as flavonoids, tannins, phenols and vitamin C which have the function of inhibiting the tyrosinase enzyme and the synthesis of melanin. The aim of this research was to prove that a 20% of Petai seed (Parkia speciosa) extract cream could prevent the increase of melanin counts in the skin of Guinea Pigs (Cavia porcellus) exposed to UV-B. Method: This research employed an experimental study through a randomized post-test only control group design that used 36 male guinea pigs (Cavia porcellus) that divided into 2 (two) groups each of which were 18 guinea pigs. In order to find out the mass, melanin stained with Masson-Fontana, the melanin count was showed in percent. The results of this research were then analyzed and used descriptive analysis, data normality, data homogeneity, and comparability tests. Results: The results indicated that the mean was 20.543 ± 3.344%, whereas, in the treatment group that smeared by 20% of petai seed extract cream, the mean value was 1.533 ± 0.518% (p <0.001). This indicated that the treatment group had a smaller melanin count than the control group. Conclusion: Based on the results of this research, it can be concluded that 20% of petai seed extract cream inhibited the increase of melanin counts in guinea pigs’ skin exposed to UV-B.